KETIKA TEKNOLOGI MENJADI TUNTUTAN: PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP TECHNOSTRESS GURU - Rizkiah Rizkiah; Dian Dwi Nur Rahmah; Netty Dyan Prastika; Edoardo Tondang (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
The acceleration of instructional digitalization, which requires mastery of a variety of independent learning applications amidst limited technical skills, is the background to this research. These operational issues trigger psychological pressure in the form of technostress, which has the potential to reduce work productivity and the mental well-being of educators. The main focus of this scientific study is to dissect and test the influence of perceived organizational support on teachers' technostress levels. The steps of this descriptive inferential quantitative research path were operated through purposive sampling of 86 active teachers at Sangatta State High School. The primary field data collection procedure was collected through the distribution of a Likert-scale questionnaire instrument with four alternative answers, which was then executed using parametric prerequisite testing and simple linear regression analysis modeling assisted by SPSS version 26 software. The quantitative data from the research empirically revealed a significant and negative influence, indicated by the F-value of 140.021 and a significance probability value of p of 0.000. The coefficient of determination (R-square) results recorded a prediction accuracy score of 0.625, which proves the real contribution of organizational support worth 62.5 percent to the variation in reducing the subject's digital stress burden. The main conclusion confirms that strengthening superior support and providing rewards has proven highly effective in improving teachers' cognitive readiness in managing techno-overload. School management is recommended to draft a strategy for ongoing, periodic digital literacy training. ABSTRAK Akselerasi digitalisasi instruksional yang mewajibkan penguasaan ragam aplikasi pembelajaran mandiri di tengah keterbatasan kecakapan teknis melatarbelakangi penelitian ini. Masalah operasional tersebut memicu tekanan psikologis berupa technostress yang berpotensi menurunkan produktivitas kerja serta kesejahteraan mental para tenaga pendidik. Fokus utama kajian ilmiah ini adalah membedah dan menguji pengaruh perceived organizational support terhadap tingkat technostress guru. Langkah-langkah jalur riset kuantitatif deskriptif inferensial ini dioperasikan melalui penarikan sampel secara purposive sampling terhadap 86 guru aktif di lingkungan SMA Negeri Sangatta. Prosedur pengumpulan data primer lapangan dihimpun lewat penyebaran instrumen kuesioner skala Likert empat alternatif jawaban, yang selanjutnya dieksekusi menggunakan pengujian prasyarat parametrik serta permodelan analisis regresi linear sederhana berbantuan perangkat lunak SPSS versi 26. Data kuantitatif hasil penelitian secara empiris menyingkap pengaruh yang signifikan dan negatif, ditunjukkan oleh perolehan nilai F-hitung sebesar 140,021 dan nilai probabilitas signifikansi p sebesar 0,000. Perolehan hasil koefisien determinasi (R-square) mencatatkan skor akurasi prediksi sebesar 0,625, yang membuktikan kontribusi nyata dukungan organisasi senilai 62,5 persen terhadap variasi penurunan beban stres digital subjek. Simpulan utama menegaskan bahwa penguatan aspek dukungan atasan serta pemberian penghargaan terbukti sangat andal meningkatkan kesiapan kognitif guru dalam mengelola hambatan techno overload. Manajemen sekolah direkomendasikan merancang draf strategi pelatihan literasi digital berkala secara berkesinambungan.